Abul Kalam Azad’s thought of inclusive theology and education for religious pluralism - Nanang Nurcholis (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
This article sheds light on Maulana Abul Kalam Azad’s ideas of inclusive theology in his phenomenal work, Tarjuman al-Qur’an, especially his commentary on surah al-fatihah. It is also aimed to describe its significance as education for religious pluralism in India in particular and in global world in general. Azad’s inclusive theology can be analyzed from his understanding on the concept of God, religion and unity of religion. This study mainly uses hermeneutical and philosophico-theological approach because inclusivism can be dealt with in philosophy, especially philosophy of religion. The finding is that God as the “cherisher” and “flourisher” (rabb) transcends all fragmentations and divisions of humanity in race, color, and religion. The path of universal God (rabb al-‘alāmīn) is “the right path” (sirāt al-mustaqīm) which belongs to no particular religion. For Azad, all religions in origin contain the truth and are pervaded with the same spirit the existing and variations in religions do not affect the essentials of religion. The outward path (shari’a, minhāj) may vary according to the circumstances. The difference between one religion and another are not differences in dīn, the basic provision, but in the manner of giving effect to it.